PENGARUH PENYAJIAN LAPORAN KEUANGAN, AKSESIBILITAS INFORMASI DESA DAN PARTISIPASI MASYARAKAT TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DI DESA UJUNG RAMBE KECAMATAN BANGUN PURBA KABUPATEN DELI SERDANG - Masdar Masdar; Mas ut Mas ut; Farida Khairani Lubis (Universitas Islam Islam Sumatera Utara, 2022)
This study aims to determine the effect of the presentation of financial statements on financial management accountability, the effect of village information accessibility on financial management accountability, the effect of community participation on financial management accountability and the effect of presenting economic reviews, village statistics accessibility and network participation simultaneously (simultaneously) on management accountability. Ujung Rambe Village, Bangun Purba District, Deli Serdang Regency. This type of research is quantitative. Data collection techniques used in this study are (1) field research (field research) obtained by means of interviews, observations (observations) and questionnaires (list of questions); and (2) literature researchThe results of statistical tests have proven that partially there is a significant and significant effect of the independent variable, namely Financial Statement Presentation on the dependent variable, namely Village Fund Management Accountability. While the variables of Village Information Accessibility on Village Fund Management Accountability and Community Participation on Village Fund Management Accountability partially have an influence and are not significant. The results of the study simultaneously showed that there was a significant effect between Financial Statement Presentation, Village Information Accessibility and Community Participation on Village Fund Management Accountability and vice versa. This is indicated by the value of F count which is greater than F table.